Penerapan Home Learning Akibat Pandemi COVID 19 di Sekolah Dasar Alam Al Izzah Junwangi Krian Sidoarjo Tahun Ajaran 2019/2020 - Arinal Haq (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
This study is intended to determine the application of home learning due to the COVID 19 pandemic in Al Izzah Nature Elementary School Krian Sidoarjo. The formulation of the problem to be answered from this research is about the concepts and processes in the preparation of home learning, the process of implementing home learning, supporters and obstacles in the application of home learning at Al Izzah Nature Elementary School Krian Sidoarjo. This research is a descriptive qualitative research that is library research and phenomenological studies. The subjects in this study were the principal, educators, parents and students at Al Izzah Nature Elementary School Krian Sidoarjo. Data collection carried out in this study is to collect literature on home learning, retrieve data through interviews and observations related to the application of home learning in Al Izzah Nature Elementary School Krian Sidoarjo The results of this study indicate that Al Izzah Nature Elementary School Krian Sidoarjo has made thorough preparations regarding the concept and arrangement of home learning during the COVID-19 pandemic. The inhibiting factors in the application of home learning are the lack of parental intensity, the lack of enthusiasm of students in running the home. learning and unstable signal fluency. The learning process during the COVID-19 pandemic at Alam Al Izzah Krian Sidoarjo Elementary School only changed places, which was carried out at home without changing the concept of school learning. The house must be able to become a place for students to learn. The learning process is carried out at home and without burdening parents in assisting students in learning. Keywords: home learning, education, pandemic, study from home